2014
DOI: 10.5897/ajar2013.7244
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of fenpropathrin residues in squash fruits intercropped with garden rocket

Abstract: The dissipation and residue of fenpropathrin in squash fruits intercropped with garden rocket under field conditions were studied. Samples were collected periodically on the sampling days after applications. The residue data revealed the half-life values of fenpropathrin in Squash fruit and garden rocket were found to be 1.78 and 1.85 days, respectively. The residues of fenpropathrin were more greatly concentrated in the squash fruit shell than that squash fruit pulp. The initial concentration level of fenprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…For both single and double the recommended dosages, the half-life of fenpropathrin in chilli following third application was found to be 2.41 and 1.92 day, respectively. Similar findings were observed by Ahmed and Mohammed (2014) who reported deposits of 1.53 and 1.76 mg/kg in squash fruit along with garden rocket following treatment of fenpropathrin 20 EC @ 238 g a.i./ha with half-life values of 1.78 days besides 1.85 days, accordingly. Singh et al (2015) suggested that spraying of cypermethrin @ 50 and 100 g a.i./ha, the residual deposits were found to be 1.46 and 3.11 mg/ kg declined below its LOQ of 0.05 mg kg -1 after 25 days with T 1/2 of 4.43 days as well as 4.70 days, respectively.…”
Section: Resultssupporting
confidence: 88%
“…For both single and double the recommended dosages, the half-life of fenpropathrin in chilli following third application was found to be 2.41 and 1.92 day, respectively. Similar findings were observed by Ahmed and Mohammed (2014) who reported deposits of 1.53 and 1.76 mg/kg in squash fruit along with garden rocket following treatment of fenpropathrin 20 EC @ 238 g a.i./ha with half-life values of 1.78 days besides 1.85 days, accordingly. Singh et al (2015) suggested that spraying of cypermethrin @ 50 and 100 g a.i./ha, the residual deposits were found to be 1.46 and 3.11 mg/ kg declined below its LOQ of 0.05 mg kg -1 after 25 days with T 1/2 of 4.43 days as well as 4.70 days, respectively.…”
Section: Resultssupporting
confidence: 88%
“…As a result, it's utilized to control a wide range of mites and insects [7]. Pests can be controlled with these chemicals as long as they comply with country regulations in the country where they are used.…”
Section: Introductionmentioning
confidence: 99%